Structural characterization of a low molecular weight Bletilla striata polysaccharide and antitumor activity on H22 tumor-bearing mice - Liu, Chao; Dai, Ke-yao; Ji, Hai-yu; Jia, Xiao-yu; Liu, An-jun (International journal of biological macromolecules, 2022)
In this study, a novel low molecular weight polysaccharide (named LMW-BSP) was extracted from Bletilla striata at 4 °C. The results of structural characteristics analysis showed that LMW-BSP was a 23 kDa neutral polysaccharide contained glucose and mannose at a molar ratio of 1.00:1.26. Structural investigations of the periodate oxidation studies, Smith-degradation as well as methylation were performed, and combined with 1D and 2D NMR spectroscopy, the main chain residues sequence of LMW-BSP was concluded to be: α-D-Manp-(1 → 3)-β-D-Manp-(1 → [4)-β-D-Glcp-(1]2 → 4)-β-D-Manp-(1 → 3)-β-D-Manp-(1→. Moreover, the antitumor activity of LMW-BSP was evaluated in H22 tumor-bearing mice. And the results suggested that LMW-BSP could effectively improve immune cells activities and lymphocytes subsets proportions dose-dependently in tumor-bearing mice, leading to the apoptosis of H22 cells via G1 phase arrested. LMW-BSP inhibited tumor growth and exhibited antitumor effects in vivo. And it supported considering the novel polysaccharide as a potential drug component in hepatocellular carcinoma treatment.